2014
DOI: 10.1038/modpathol.2013.244
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cancer-testis antigens MAGEA1, MAGEA3, ACRBP, PRAME, SSX2, and CTAG2 in myxoid and round cell liposarcoma

Abstract: Myxoid and round-cell liposarcoma is a frequently encountered liposarcoma subtype. The mainstay of treatment remains surgical excision with or without chemoradiation. However, treatment options are limited in the setting of metastatic disease. Cancer-testis antigens are immunogenic antigens with the expression largely restricted to testicular germ cells and various malignancies, making them attractive targets for cancer immunotherapy. Gene expression studies have reported the expression of various cancer-testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 46 publications
0
50
0
Order By: Relevance
“…Among the up‐regulated genes, we focused on the cancer‐testis antigen PRAME . MLS samples were recently reported to show a high level of PRAME expression, and other recent studies demonstrated that another cancer‐testis antigen, NY‐ESO‐1 ( CTAG1B ), was hyper‐expressed in MLS . In our microarray results, 111 cancer‐testis antigens were included, and eight cancer‐testis antigens were up‐regulated by more than fourfold compared to their levels in normal adipose tissue (Table ).…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…Among the up‐regulated genes, we focused on the cancer‐testis antigen PRAME . MLS samples were recently reported to show a high level of PRAME expression, and other recent studies demonstrated that another cancer‐testis antigen, NY‐ESO‐1 ( CTAG1B ), was hyper‐expressed in MLS . In our microarray results, 111 cancer‐testis antigens were included, and eight cancer‐testis antigens were up‐regulated by more than fourfold compared to their levels in normal adipose tissue (Table ).…”
Section: Resultsmentioning
confidence: 58%
“…Recently published studies have reported that NY-ESO-1 was expressed in 100% (25/25) and 89% (16/ 18) of the MLS samples, and in 10% (1/10) of the DDLS, none (0/10) of the WLS and 50% (3/6) of the PLS samples and that PRAME was expressed in 100% of 37 MLSs by immunohistochemistry [19][20][21]. Our data are nearly coincident with these results and, as with NY-ESO-1, PRAME was highly expressed in the MLSs among the liposarcomas in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytotoxic T lymphocytes (CTL) are critical effectors of tumor cell killing in animal models, and intense CTL infiltration correlates with good prognosis in sarcomas (43,44). To stimulate CTL responses, MHCI-directed peptide vaccines have been pursued extensively, (45,46). Trials of such vaccines have historically shown disappointing clinical effects (47), likely due in part to insufficiency of vaccine adjuvants but also to the mutability of advanced cancers and to mechanisms of immunoevasion.…”
Section: Advances In Immunotherapymentioning
confidence: 99%
“…[54] Melanocytic lesions Melanoma 9/16 (56%)/RT-PCR [67] 5/10 (50%)/nested RT-PCR [68] 4/5 (80%)/RT-PCR [69] 72/105 (69%)/RT-PCR [70] Metastatic tumor 110/145 (76%)/RT-PCR [71] Primary tumor 36/100 (36%)/RT-PCR Metastatic tumor 2/3 (67%)/RT-PCR [72] Primary tumor 1/4 (25%)/RT-PCR 7/12 (58%)/RT-PCR [26] Malignant melanomas 12/23 (52%)/RT-PCR [73] Malignant 18/28 (64%)/RT-PCR 14/31 (45%)/FACS [74] 3 primary, 21 metastasis 11/24 (46%)/RT-PCR [32] Lymph node metastasis 35 [76] Sentinel node 25/53 (47%)/qRT-PCR [77] Sentinel node from melanoma free patients 24/55 (44%)/RT-PCR [78] Primary tumor 4/10 (40%)/RT-PCR Sentinel node from melanoma patients 12/17 (71%)/RT-PCR 111/202 (55%)/RT-PCR [79] Esophageal mucosa 6/6 (100%)/IHC/M3H67 [80] Metastatic tumor 116/191 (61%)/IHC/57B [81] CTL: Cytotoxic T lymphocyte; ELISA: Enzyme-linked immunosorbent assay; IHC: Immunohistochemistry; mAb: Monoclonal antibody; (q)RT-PCR: (Quantitative) reverse transcription PCR; TIL: Tumor-infiltrating lymphocyte. [83] 'In situ' melanoma 0/3 (0%)/RT-PCR [72] Benign melanocytic nevus 0/10 (0%)/RT-PCR Nevus 0/19 (0%)/IHC/M3H67 [83] Dysplastic nevus 0/14 (0%)/RT-PCR 0/4 (0%)/RT-PCR [71] Benign nevocellular nevus 0/12 (0%)/RT-PCR [37] Primary tumor 9/26 (35%)/RT-PCR [32] Primary tumor 7/51 (14%)/RT-PCR [73] Primary tumor 37/362 (10%)/qPCR [85] Neuroblastoma Primary tumor 23/47 (49%)/RT-PCR [86] Gastrointestinal stromal tumor 7/86 (8%)/IHC/M3H67 [87] 5/35 (14%)/IHC/M3H67 [88] Gastric cancer 12/12 (100%)/qRT-PCR [90] Sarcoma Osteosarcoma 28/28 (100%)/qRT-PCR [91] Myxoid and round cell liposarcoma 2/8 (25%)/qRT-PCR [92] CTL: Cytotoxic T lymphocyte; ELISA: Enzyme-linked immunosorbent assay; IHC: Immunohistochemistry; mAb: Monoclonal antibody; (q)RT-PCR: (Quantitative) reverse transcription PCR; TIL...…”
Section: Ihc/b57mentioning
confidence: 98%